Framework for the Implementation Procedures of Relocation and Conservation of the Kampung Laut Old Mosque: A Contractor’s Perspective - Hanafi, Mohd Hanizun; Abdullah, Shardy; Ahmad Rashid, Zul Zakiyuddin (International Journal of Sustainable Construction Engineering and Technology, 2023)
A high value building that is one of the early signs of the arrival of Islam to Malaysia and Southeast Asia is the Kampung Laut Old Mosque (KLOM). The mosque has been relocated to its original location, Kampung Laut, Tumpat to re-assimilate the original culture and landscape of its construction. The experience of implementing procedures for the relocation and retention of these heritage values should be gained as much as possible by the stakeholders of the construction industry. It can be used as one of a solid foundation to strengthen the role of the construction industry as a trigger for the development of other industries such as tourism; hence the economy of a country. At the same time, it is able to maintain the heritage values of the special buildings of the KLOM. Therefore, the objective of this study is to develop a framework for the implementation procedures for the relocation and conservation of the heritage values of the KLOM. Structured interviews were conducted with fourteen (14) respondents directly involved in the successful relocation and conservation of the heritage values of this mosque. This study revealed four (4) main categories containing eighteen (18) sub-categories belong to the independent variables. These independent variables will significantly affect the dependent variables in performing the procedure. This study also reveals four (4) elements of dependent variables in the procedure of relocation and conservation of heritage values of the KLOM, namely cost, quality, time and scope. The formation of this framework has revealed the holistic implementation procedure of a special building such as the KLOM. It is capable of being manipulated by stakeholders to implement such procedures effectively on other specialty constructions. In turn, it is able to increase the competitiveness of the construction industry to effectively contribute to the economy of a country.